Creating Risk Takers: When teachers support students and create a caring classroom culture, they enable students to take risks. The National Teacher of the Year offers advice on how to make it happen. Issue 3 (February 2015) - McComb, Sean
The author, the 2014 National Teacher of the Year, discusses why it's important to create a caring classroom culture and shares his strategies for doing so.